Scale of potential indicators of organizational representation: EIPRO - de Miguel Calvo, Jesús María (2003)
The investigation report presents/displays the process of construction of an instrument of measurement for the study of the organization like reality socially constructed, concretely the phases to identify, to isolate and to discriminate the indicators of the phenomenon that we have denominated organizational representation. The boundary of the potential indicators has been made using technical qualitative (documentary analysis, diagram of affinity, agreement interjudges -conceptual). The potential indicators belong to anyone of the seven following dimensions: organizational context, structure, processes, climate, culture, satisfaction, effectiveness. The isolation and discrimination of the indicators selected between the potentials have been made using technical quantitative statistics (descriptive analyses, multidimensional scaling, factorial analysis and reliability indices). 49 indicators have been selected that constitute, to investigation level, the used independent variables for the study of the organization like social construction. Their imminent unfolding in elements (ítems) measurable (by means of techniques you will climb) constitutes the informative base of the Questionnaire of Representation Organizational CREO©.